THE IMPORTANCE OF CHARACTER EDUCATION IN SHAPING THE POSITIVE BEHAVIOR OF ELEMENTARY SCHOOL STUDENTS - Warlim Warlim; Dr. Suryaningsih, S.S., M.Pd.K.; Hasni Noor (INJOSEDU: International Journal of Social and Education, 2025)
Character education in primary schools is an important element in the formation of a generation that behaves positively and responsibly. This education aims to instill moral and ethical values early on, so that students are able to distinguish between right and wrong and develop positive behaviors in everyday life. In addition, character education also serves to develop essential social skills, such as the ability to communicate, work together in teams, and resolve conflicts in a peaceful manner. These social skills are essential for building harmonious relationships and effective functioning of students in various social situations. By having a good moral, ethical and social skills foundation, students are able to adapt and contribute positively in their environment. In conclusion, character education in primary schools is an integral part of the curriculum that not only strengthens academic aspects but also shapes individuals with good character and morals. Therefore, it is important for educational institutions to ensure that character education is prioritized in the learning process in primary schools, in order to create the next generation with noble character and positive mentality.